Dentistry for the child and adolescent - McDonald, Ralph E.; Avery, David R. (London The C.V. Mosby Company, 1983)
The book provides current diagnostic and treatment recommendations based on research and clinical experience. The information is relevant to the practice to the practice of pedodontics.
Keywords: Răng Hàm Mặt